2019
DOI: 10.1080/20786190.2019.1664085
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with physical activity amongst patients with hypertension in two community health centres in uMgungundlovu health district, KwaZulu-Natal, 2018

Abstract: Background: Hypertension (HPT) is a global public health challenge. It predisposes to cardiovascular diseases, kidney diseases and disability as well as contributing to high death rates. HPT is increasing tremendously in sub-Saharan Africa with HPT-related mortality risk having increased by 25% in less than 10 years in South Africa. Physical activity is a cost-effective way of reducing, controlling and preventing hypertension. The aim of the study was to establish the level of physical activity, and factors as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
2
7
1
2
Order By: Relevance
“…Having other commitments, poor physical health, lack of access to exercise facilities and easily accessible transportation were main barriers to physical activity for the patients. Consistent with the findings of the current study, Mbambo et al identified that health problems and having no time are major barriers to physical activity in South Africa (Mbambo et al., 2019 ). In line with the findings of the current study, a study from Iran revealed tiredness, physical problems and being busy at work are barriers to physical activity among patients (Sabzmakan et al., 2014 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Having other commitments, poor physical health, lack of access to exercise facilities and easily accessible transportation were main barriers to physical activity for the patients. Consistent with the findings of the current study, Mbambo et al identified that health problems and having no time are major barriers to physical activity in South Africa (Mbambo et al., 2019 ). In line with the findings of the current study, a study from Iran revealed tiredness, physical problems and being busy at work are barriers to physical activity among patients (Sabzmakan et al., 2014 ).…”
Section: Discussionsupporting
confidence: 90%
“…Improving patients' health literacy is important to increase their understanding about heart disease and associated health behaviours (Aaby et al., 2017 ; Boateng et al., 2017 ; Mbambo et al., 2019 ; Tchicaya et al., 2018 ). The current study shows patients have inadequate knowledge about heart disease, despite being at high risk, and this is in accordance with findings from reviews of evidence from South Africa (Surka et al., 2015 ), Tanzania (Hertz et al., 2019 ) and sub‐Saharan African (Boateng et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sedavý spôsob života je jedným z hlavných rizikových faktorov KVO nezávislých od účasti na PA (Lee et al, 2012). Súhlasíme s tvrdením autorov Mbambo et al (2018), ktorí uvádzajú, že PA je nákladovo nenáročný, praktický, prirodzený a efektívny spôsob kontroly hypertenzie, ale aj väčšiny ostatných KVO. Vyššie uvedení autori poukazujú na štúdie, ktoré preukázali priaznivé účinky cvičenia na hypertenziu so znížením systolického a diastolického tlaku krvi až o 5 -7mmHg.…”
Section: Infarkt Myokardu -Charakteristika a Klasifikáciaunclassified
“…TK -krvný tlak, TKS -TK systolický, TKD -TK diastolický, HT -hypertenzia Vo väčšine krajín trend prevalencie hypertenzie stúpa(Xu et al, 2016). Táto choroba predstavuje podľaMbambo et al (2018) najmenej 45% úmrtnosti na srdcové choroby a 51% úmrtnosti na mozgové príhody. Podľa týchto autorov označuje aj ako tichý zabijak; asi 50% ľudí so zvýšeným krvným tlakom to nevie, pretože sa u nich nevyskytujú žiadne príznaky.…”
unclassified
“…Individuals with high SE can effectively apply skills to motivate themselves to sustain their behavior when facing barriers (Bandura, 1987). For instance, individuals with high SE are likely to use goal-setting skills to motivate themselves to overcome personal barriers, such as lack of time, to achieve their goal of sustaining PA (Mbambo et al, 2019). Another SCT construct, OE, influences individuals' motivation to engage in positive behavior (Bandura, 1998).…”
Section: Introductionmentioning
confidence: 99%